If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3n + 1 = 28 Reorder the terms: 1 + 3n = 28 Solving 1 + 3n = 28 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 3n = 28 + -1 Combine like terms: 1 + -1 = 0 0 + 3n = 28 + -1 3n = 28 + -1 Combine like terms: 28 + -1 = 27 3n = 27 Divide each side by '3'. n = 9 Simplifying n = 9
| 3(x+4)=26 | | 91=6w-15w-19 | | x(x+6)=9x^2+3 | | 3/-2x=2/3x-13 | | 8=2x-6/4 | | 6=2u+42+2u | | 10-4abs(3x+2)=0 | | =-16x^2+27x-10 | | (7-5i)(4-7i)= | | 7x+8=x | | (-9v+4)=15 | | 6(12+5r)=5r+7(2r+4) | | 7/4x-5/2=1 | | 8*x^2-65*x+8=0 | | -20P-5(4-5P)=2(P-3)-20 | | (83-x)+(5x+11)=180 | | (I)(5i)(4-3i)= | | (83-x)+(5x+11)=10 | | (3x+2)(2x-1)=-(3x+1) | | 7y+9=6y-2 | | 645-07-04-00-00_files/i0090000.jpg | | (83-x)=180 | | 3=x/3.3 | | (0,29x)/(0,4-0,4x^2,39) | | x/6=3/4 | | x^8+254x^4+1=0 | | (5x+11)=180 | | (M-9)+6=4(m-2)-2(m-6) | | 2x+13=-5x-7x | | 18a/6 | | (7+5i)+(5i)= | | (x-2x/100)*60/100*70/100=7203 |